A peripheral subepithelial network for chemotactile processing in the predatory sea slug Pleurobranchaea californica. - Tigran Norekian; Yichen Liu; Ekaterina D Gribkova; Jilai Cui; Rhanor Gillette (PLoS ONE)
Many soft-bodied animals have extensive peripheral nervous systems (PNS) with significant sensory roles. One such, the sea slug Pleurobranchaea californica, uses PNS computations in its chemotactile oral veil (OV) in prey tracking, averaging olfactory stimuli across the OV to target likely source direction, or "stimulus place". This suggests a peripheral subepithelial network (SeN) interconnecting sensory sites to compute the directional average. We pursued anatomy and connectivity of previously described ciliated putative sensory cells on OV papillae. Scanning electron microscopy (SEM) confirmed paddle-shaped cilia in clusters. Anti-tubulin and phalloidin staining showed connections to branching nervelets and muscle fibers for contraction and expansion of papillae. Ciliary cell processes could not be traced into nerves, consistent with sensory transmission to CNS via secondary afferents. Anti-tyrosine hydroxylase-stained ciliated cells in clusters and revealed an at least partially dopaminergic subepithelial network interconnecting clusters near and distant, connections consistent with PNS averaging of multiple stimulated loci. Other, unidentified, SeN neurotransmitters are likely. Confirming chemotactile functions, perfusible suction electrodes recorded ciliary spiking excited by both mechanical and appetitive chemical stimuli. Stimuli induced sensory nerve spiking like that encoding stimulus place. Sensory nerve spikes and cilia cluster spikes were not identifiable as generated by the same neurons. Ciliary clusters likely drive the sensory nerve spikes via SeN, mediating appetitive and stimulus place codes to CNS. These observations may facilitate future analyses of the PNS in odor discrimination and memory, and also suggest such SeNs as potential evolutionary precursors of CNS place-coding circuitry in the segmented, skeletonized protostomes and deuterostomes.